The Research Progress in Immunotherapy of Tuberculosis - Mi, Jie; Liang, Yan; Liang, Jianqin; Gong, Wenping; Wang, Shuyong; Zhang, Junxian; Li, Zhiming; Wu, Xueqiong (Frontiers in Cellular and Infection Microbiology, 2021)
Tuberculosis (TB) is a serious public health problem worldwide. The combination of various anti-TB drugs is mainly used to treat TB in clinical practice. Despite the availability of effective antibiotics, effective treatment regimens still require long-term use of multiple drugs, leading to toxicity, low patient compliance, and the development of drug resistance. It has been confirmed that immune recognition, immune response, and immune regulation of Mycobacterium tuberculosis (Mtb) determine the occurrence, development, and outcome of diseases after Mtb infection. The research and development of TB-specific immunotherapy agents can effectively regulate the anti-TB immune response and provide a new approach toward the combined treatment of TB, thereby preventing and intervening in populations at high risk of TB infection. These immunotherapy agents will promote satisfactory progress in anti-TB treatment, achieving the goal of "ultra-short course chemotherapy." This review highlights the research progress in immunotherapy of TB, including immunoreactive substances, immunotherapeutic vaccines, chemical agents, and cellular therapy.